Enhancing ESG Performance Through Ownership Structure, Stakeholder Engagement, and Sustainable-Responsible Investment - Geraldina, Ira; Muktiyanto, Ali; Na'im, Ainun (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study analyzes how ownership, stakeholder engagement, and Sustainable and Responsible Investment affect ESG performance. Ownership is classified by government, management, and minority shareholder, while stakeholder engagement by employee, creditor, and community. Socially Responsible Investment is measured by dummy variable of SRI Kehati Stock Index. This analysis uses 270 Indonesia Stock Exchange-listed company observations from 2012–2022. Using unbalanced panel data, study finds that Socially Responsible Investment improves ESG performance, although ownership type has a distinct effect. ESG suffers from stakeholder engagement, particularly creditor and community engagement. This investigation advances ESG antecedent that interplays shareholders, industry recognition, and stakeholder’s engagement.